Screenplay as Translation: An Intergenric Translation of Intralingual Dynamics in Tamil - Gayathree, S. (University of Jaffna, 2025)
This study explores the process of intergenric translation, with particular emphasis on screenplay as a medium that operates at the intersection of text and audiovisual expression. Translation is not merely a linguistic process but also a semiotic process which involves a shift from one set of signs to another, often crossing boundaries of media, genre, and culture. In this context, the screenplay serves as a rich site of investigation. Functioning both as a written text and as a blueprint for cinematic realization, the screenplay represents a hybrid form that embodies both literary and performative dimensions. Screenplays may be original, translated or inspired by pre-existing texts. Whether derived from a novel, a folk tale, a biography, or even a newspaper report, the screenplay mediates content through a distinct semiotic lens, converting verbal narrative into visual and auditory language. Despite being often seen as secondary to the film itself, the screenplay holds an autonomous textual identity. It plays a crucial regulatory and predictive role in film production by providing structural coherence. This paper argues that screenplays can be studied both as products of translation and as sites of translational activity. They exemplify not only the conversion of one language into another but also the transformation of ideas, moods, and atmospheres across media and genres. The study focuses on Utirippukkal, a Tamil screenplay that demonstrates intralingual and intracultural translation. This text is used as a case study to analyze how semiotic relationships function in screen adaptation and how elements from the original milieu are preserved, altered, or re- signified through cinematic rendering. As a screenplay moves through different stages from written word to visual scene, from literary source to performative script, it accumulates marks, traces, and imprints of various discursive contexts. These layered elements constitute a semiotic archive, allowing for the study of inter-generic dynamics in the translation process. Utirippukkal illustrates how cultural specificity, character nuance, and social context are managed and negotiated within the screenplay and carried through to the screen. By examining the interconnectedness of screenplay and translation, both as processes of meaning-making and as final products, this paper contributes to broader discussions in Translation Studies, Media Studies, and Semiotics. It emphasizes the creative agency of the screenwriter, particularly in translations, where the act of translation becomes not just a transfer but a transformation. The screenplay, then, emerges as a key artifact in the inter-semiotic translation of narratives, offering insights into the complex journey of stories as they move across languages, modes, and cultural expressions.
Keywords: Screenplay; Inter-semiotic translation; Semiotics of media